Groundwater Quality and the Settlements Condition in - Munawar Cholil (Forum Geografi, 1996)
To comprehend the factors which influence on the juvenile water, it needs paying attention to the rocks permeability, the thickness of the aeration zone, the type of the material composition and the depth of the ground water. The grade of the ground water quality, both ground water in general and juvenile water in the urban, is dependent upon the natural physical, man made physical, and the condition of the local inhabitant besides the another factors. The influence grade of the factors are undersirable yet because among of them there are cross-linkages. The linkage of the ground water quality condition, besides another factor, inconfirmed by the inhabitant and the settelement. The aspect of the man made physical, both sanitation condition and the population density with their activity effect i.e. sewage by product, should fully determine the ground water quality. There is a closed connection between the juvenile water quality and the settlement condition, mainly, in the case is the domestic sewage disposal. It is estimated that the unit of settlement associates with the grade of the juvenile water quality. Some of the variabilities which are desirable to sustain the settlement condition and constitutes the influence variability i.e. the density of the population and buildings, and the condition of the drainage system for sewage.